What European Union in the “Age of Uncertainty”? Weathering the Geopolitical Storms in a World of Perpetual Crises - Isabelle Ioannides (Intereconomics)
Abstract A world of risks and uncertainties can also be a world of opportunities. How and how quickly the EU adapts to the socio-political, economic, energy and climate transitions at hand, and how it responds to geopolitical shifts and shocks, will determine whether it can sustain its role and standing on the international stage.